Effects of ozone nano-bubble water on mucositis induced by cancer chemotherapy - Hayashi, Kamichika (Biochem Biophys Rep, 2019)
No effective, reliable treatment for stomatitis associated with cancer therapy has been established. This study focused on the its effectiveness of ozone nano-bubble water (ONBW) for the treatment of chemotherapy-induced stomatitis. Oral mucositis was induced in 14-week-old male Sprague-Dawley rats (N = 21). The animals were randomly divided into 3 groups: 7 without treatment (control); 7 treated with physiological salt solution (saline); and 7 treated with ONBW. Animals were weighed on Days 7, 9, 11, and 16. Stomatitis grade evaluation and bacterial count measurements were performed before rinsing in all animals 3, 5, and 10 days after acetic acid irritation (Days 9, 11, and 17 respectively). Weight loss after stomatitis creation was observed in all groups, with significant differences between the control and ONBW groups and between the saline and ONBW groups on Day 16. The stomatitis grade did not worsen during the experimental period in any group, with the lowest grades in the ONBW group on Days 11 and 16. Significant differences were identified between the control and ONBW groups and between the saline and ONBW groups on Days 11 and 16. Oral bacterial counts tended to decrease over time in all three groups, with the greatest decrease in the ONBW group, followed by the saline group. The decrease in the bacterial count was steepest in the ONBW group. Rinsing out the oral cavity with ONBW decreased bacterial counts and encouraged the healing of oral chemotherapy-induced stomatitis. ONBW may be an effective treatment for chemotherapy-induced stomatitis.